Non-pharmacological management of osteoporotic vertebral fractures: Patient perspectives and experiences. (May 2023) - Tibert, Nicholas; Ponzano, Matteo; Brien, Sheila; Funnell, Larry; Gibbs, Jenna C; Jain, Ravi; Keller, Heather; Laprade, Judi; Morin, Suzanne N; Papaioannou, Alexandra; Weston, Zach; Wideman, Timothy Howard; et al.
Objective: To understand perceptions on rehabilitation after vertebral fracture, non-pharmacological strategies, and virtual care from the perspective of individuals living with vertebral fractures. Design and setting: We conducted semi-structured interviews online and performed a thematic and content analysis from a post-positivism perspective. Participants: Ten individuals living with osteoporotic vertebral fractures (9F, 1 M, aged 71 ± 8 years). Results: Five themes emerged: pain is the defining limitation of vertebral fracture recovery; delayed diagnosis impacts recovery trajectory; living with fear; being dissatisfied with fracture management; and "getting back into the game of life" using non-pharmacological strategies. Conclusion: Participants reported back pain and an inability to perform activities of daily living, affecting psychological and social well-being. Physiotherapy, education, and exercise were considered helpful and important to patients; however, issues with fracture identification and referral limited the use of these options. Participants believed that virtual rehabilitation was a feasible and effective alternative to in-person care, but perceived experience with technology, cost, and individualization of programs as barriers.